JESOCIN_MARET-2025_Vol2-No 03 - Afferdhy Ariffien; Diah Fatma Sjoraida (Journal of Jabar Economic Society Networking Forum, 2025)
This conceptual paper develops an integrative framework for institutional connectivity and MSME innovation capability in micro, small, and medium enterprises (MSMEs). It synthesizes established literature on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial ecosystems. The analysis explains how environmental sensing, opportunity evaluation, rapid decision making, resource flexibility, and organizational learning can be organized into proportionate managerial routines. No primary survey, interview, experimental, or statistical data are claimed. The framework proposes diagnosis, capability mapping, bounded experimentation, evidence review, governance, resource reconfiguration, and learning retention as a cumulative cycle.